Will There Be Future Deceleration? A Study of Particle Creation Mechanism in Nonequilibrium Thermodynamics - Supriya Pan; Subenoy Chakraborty (Advances in High Energy Physics)
The paper deals with nonequilibrium thermodynamics based on adiabatic particle creation mechanism with the motivation of considering it as an alternative choice to explain the recent observed accelerating phase of the universe. Using Friedmann’s equations, it is shown that the deceleration parameter (q) can be obtained from the knowledge of the particle production rate (Γ). Motivated by thermodynamical point of view, cosmological solutions are evaluated for the particle creation rates in three cosmic phases, namely, inflation, matter dominated era, and present late time acceleration. The deceleration parameter (q) is expressed as a function of the redshift parameter (z), and its variation is presented graphically. Also, statefinder analysis has been presented graphically in three different phases of the universe. Finally, two noninteracting fluids with different particle creation rates are considered as cosmic substratum, and deceleration parameter (q) is evaluated. Whether more than one transition of q is possible or not is examined by graphical representations.